Recent developments and advances in artificial saturable absorber for mode-locking in fiber lasers - Yu Chen; Sin Jin Tan; Sulaiman Wadi Harun; G. Vinitha; Truong Khang Nguyen; Zian Cheak Tiu (Results in Engineering)
In this work, we review recent work developments in artificial saturable absorbers (SAs) for ultrafast fiber lasers. The working principles of each technique, namely nonlinear polarization rotation (NPR), nonlinear optical loop mirror (NOLM) and nonlinear multimode interference (NL-MMI), are elaborated in detail. Publications from the past five years are compiled for each technique, covering a broad wavelength range from 1 µm, to 3 µm. Notable works are highlighted to showcase the advancements of artificial SAs ultrafast lasers. At the end of this review, challenges are outlined, and future research directions are suggested for continued development and industrial growth in the field of mode-locked fiber laser using artificial SAs.